CONFLICT-SENSITIVE JOURNALISM AND THE NIGERIAN PRINT MEDIA COVERAGE OF JOS CRISIS, 2010-2011. (2015)
The recent upsurge of crises in parts of Northern Nigeria has generated concerns in literature with specific reference to the role of the media in fuelling crises in the region. Previous studies on the Nigerian print media coverage of the Jos crisis focused on the obsolescent peace journalism perspective, which emphasises the suppression of conflict stories, to the neglect of the UNESCO Conflict-sensitive Journalism (CSJ) principles. These principles stress sensitivity in the use of language, coverage of peace initiatives, gender and other sensitivities, and the use of conflict analysis tools in reportage. This study, therefore, examined the extent to which the Nigerian print media conformed to these principles in the coverage of the Jos violent crisis between 2010 and 2011. The study adopted the descriptive research design and was guided by the theories of social responsibility, framing and hegemony. Content analysis of newspapers was combined with In-depth Interviews (IDIs) with 10 Jos-based journalists who covered the crisis. Four newspapers – The Guardian, The Punch, Daily Trust and National Standard were purposively selected over a period of two years (2010-2011) of the crisis. A content analysis coding schedule was developed to gather data from The Guardian (145 editions with 46 stories), The Punch (148 editions with 85 stories), Daily Trust (148 editions with 223 stories) and National Standard (132 editions with 187 stories) totalling 573 editions which yielded 541 stories for the analysis. Four forms of language use: inflammatory, conciliatory, moderate, and sensational were identified. Items in the newspapers that contained inflammatory language were 32.2%; while 30.5% were conciliatory; moderate had 26.0% and 11.3%.were sensational. The high percentage of inflammatory and sensational language at 43.2% is capable of escalating the Jos crisis. Only 29.6% of the items focused on peace initiatives. The items that focused on crisis were 70.1% while other themes had 0.4% showing the predilection of the newspapers to be transfixed on the scene of violence without seeking solutions. The items lacked gender-sensitivity featuring 88.0% male and 5.9% female speakers while 6.1% were either from institutional or unidentified sources. The absence of gender-sensitivity confirms previous studies on the relegation of the usually conciliatory female voices in conflict situations. The privately-owned Daily Trust blamed the indigenes; the Plateau State Government owned National Standard blamed the Hausa/Fulani settlers for the crisis in an unconcealed pander to proprietorial interests while The Guardian and The Punch refrained from apportioning blames. The IDIs did not show the use of conflict analysis tools by any of the newspapers although journalists claimed awareness of the UNESCO initiative. Journalists list poor remuneration, personal insecurity, and lack of insurance cover as challenges hampering their optimum performance. The predominant use of inflammatory language, scant focus on peace initiatives, gender insensitivity and failure to use conflict analysis tools contributed to the cycle of reprisal attacks characterising the Jos crisis of 2010 and 2011. The adoption and domestication of the UNESCO principles on conflict-sensitive reporting by training institutions and a consistent on-the-job training programme will ameliorate the deficits identified